Analysis Of Good Corporate Governance, Liquidity, And Company Size On The Quality Of Financial Reports - Nugraheni, Novita (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study intends to examine how firm sizes, liquidity, and effective corporate governance affect financial statements. In this study, agency theory is employed. The study's independent variables include the size of the organization, liquidity, and excellent corporate governance. The quality of the financial reports is one of the research's dependent variables. Consumer products firms that floated on the Indonesia Stock Exchange between 2019 and 2021 make up the sample for this study. SPSS is employed in the quantitative research methodology. The linear regression analysis method is used in this study. This study will demonstrate effective corporate governance and the effects of firm size on the reliability of financial reports. In the meanwhile, the quality of financial reports is unaffected by liquidity.